2020
DOI: 10.33549/physiolres.934198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perinatal hypoxia on the developing brain

Abstract: Perinatal hypoxia is still one of the greatest threats to the newborn child, even in developed countries. However, there is a lack of works which summarize up-to-date information about that huge topic. Our review covers a broader spectrum of recent results from studies on mechanisms leading to hypoxia-induced injury. It also resumes possible primary causes and observed behavioral outcomes of perinatal hypoxia. In this review, we recognize two types of hypoxia, according to the localization of its primary cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…Motor disabilities and memory damage Golan et al, 2004 executive functioning disorder and object recognition disorder (Delcour et al, 2012a;Smith et al, 2016;Piesova and Mach, 2020). In animal models, the effects of hypoxia on behavior are similar to those of ADHD.…”
Section: Modified Offspring Brain Morphologymentioning
confidence: 99%
See 3 more Smart Citations
“…Motor disabilities and memory damage Golan et al, 2004 executive functioning disorder and object recognition disorder (Delcour et al, 2012a;Smith et al, 2016;Piesova and Mach, 2020). In animal models, the effects of hypoxia on behavior are similar to those of ADHD.…”
Section: Modified Offspring Brain Morphologymentioning
confidence: 99%
“…In animal models, the effects of hypoxia on behavior are similar to those of ADHD. Animals often exhibit motor and learning disabilities, hyperactivity disorder, and decreased memory, socialization, and attention (Piesova and Mach, 2020).…”
Section: Modified Offspring Brain Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxic-ischemic injury (HII), which occurs in 1-6/1000 live full-term births, results in increased risk for neonatal mortality and later neurodevelopmental disabilities [1,2]. The hippocampal formation, a well-known functional entity fundamental for explicit memory functions (e.g., [3][4][5]), is particularly susceptible to perinatal HII (for reviews, see [6,7]). Although many previous human studies have demonstrated atrophy of the hippocampal formation and memory impairments following HII [8][9][10][11][12][13][14][15][16], these alterations have not been noted to occur until school age [17].…”
Section: Introductionmentioning
confidence: 99%